Re-imagining Transformative Pedagogies in Higher Education for Social Change and Equity - Dyantyi, Ntsika; Mkabile-Masebe, Bulelwa (CV Sinergi Ilmu dan Publikasi, 2025)
In the context of growing inequalities and diverse student populations, traditional pedagogical models often fail to address the complex socio-economic and cultural realities students face. This qualitative conceptual discourse argues that student-centred learning, critical thinking, reflexivity, and collaborative and participatory learning approaches are crucial for cultivating inclusive learning environments that empower all students, particularly those from marginalised communities. The study findings revealed that these approaches enhance social awareness and responsibility, promote inclusivity and diversity, and empower marginalised communities. Ultimately, this paper recommends that re-imagined transformative pedagogies should prioritise inclusive curricula, active and collaborative learning, and culturally responsive teaching to foster social change and equity in higher education. Higher Education Institutions (HEI) must integrate technology thoughtfully, promote student agency, and engage with communities. For long-term success, continuous professional development for lecturers and institutional policy changes are essential. This aligns with the Agenda 2063 and the Sustainable Development Goals (Goal 4) by promoting quality education, inclusive education, reducing inequalities, and fostering social change, contributing to Africa's development and global equity.